A comparative study on the failure analysis of field failed high voltage composite insulator core rods and recommendation of composite insulators: A review. (August 2022) - Ogbonna, Victor E.; Popoola, Patricia I.; Popoola, Olawale M.; Adeosun, Samson O.
Highlights: The study based on the failure analysis of high voltage composite insulator core rods. The failure mechanism of insulator core rods and it causes were discuss. The study was concluded with recommendations. Abstract: The adoption of composite insulators on high voltage power transmission lines remains the state of the art in electricity transmission/distribution, owing to their excellent electrical insulation, mechanical strength-to-weight ratio, anti-pollution flashover properties, ease of installation, and maintenance. However, long-term exposures of the composite insulators to mechanical and environmental stresses have been a major challenge to the power industries. Thus, the various fracture failure form of composite insulator core rods, such as interfacial bonding defects, brittle fractures, and decay-like fractures in association with these stresses was discussed in the review study. Furthermore, as the fracture failure of composite insulator rods affects the stable and safe operation of power lines, the authors, however, concluded the study with recommendations for better practice of power transmission lines using composite insulators. As such, the review will also give a reference for further research in this area.